Amplification of luminescence of stable radicals by coordination to NHC–gold(i) complex. Issue 15 (1st February 2022) - Hattori, Yohei; Kitajima, Ryota; Matsuoka, Ryota; Kusamoto, Tetsuro; Nishihara, Hiroshi; Uchida, Kingo
Abstract : The 4% fluorescence quantum yield of F2 PyBTM radical in dichloromethane was enhanced up to 36% by coordination to Au I with N -heterocyclic carbene ligand. Abstract : The luminescence of stable radicals can be enhanced by coordination to metal complexes. The 4% fluorescence quantum yield of (3, 5-difluoro-4-pyridyl)bis(2, 4, 6-trichlorophenyl)methyl radical (F2 PyBTM) in dichloromethane was enhanced up to 36% by coordination to Au I with N -heterocyclic carbene ligand, which is a record for metal-radical complexes.